Comment on "towards a differential equation for the nonrelativistic ground-state electron density of the He-like sequence of atomic ions" - Serra, Pablo (2006)
In a recent paper (Phys. Rev. A 71, 042501 (2005))Howard and March presented the exact ground state wave function of the spherical He-like atom, and many physical aspects of this solution were analyzed. We show that this function is not the exact solution of the model